Efektivitas Permainan Memori Matching Card Terhadap Peningkatan Kosa Kata (Wortschatz) Bahasa Jerman Siswa Kelas XI SMA YP HKBP Pematang Siantar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This study aims to see the effectiveness of the memory card matching game on increasing German vocabulary (Wortschatz) of Class XI Students of SMA YP HKBP Pematang Siantar. This research used quantitative method with experimental approach and One Group Pretest-Posttest research design. The population in this study were class XI students totaling 34 people. The sample used was 19 people, namely students of class XI IPA SMA YP HKBP Pematang Siantar. The conclusion of this study, namely the Matching Card learning media on increasing German vocabulary (Wortschatz) of XI science class students of SMA YP HKBP Pematang Siantar. This is evidenced by an increase in the average score of students at the time of the pretest of 48.68 below the KKM and at the time of the posttest to 87.00 above the KKM. Based on the results of data analysis and hypotheses tested, it is known that the Matching Card learning media is effective on students' writing skills. This is evidenced by the results of the normalized N-Gain test analysis with a score of 0.7705 or equivalent to 77%, where the score is in the effective category. Then based on the statistical hypothesis test with paired samples test, the significance value is 0.001 <0.05 in the sense that the calculated statistical results (t output number) < table statistics (t table), it is concluded that Ho is rejected and H₁ is accepted. Thus, the Matching Card learning media has an effect in the effective category on the learning process.